The way out for urban household solid waste classification in China: From the perspective of multi-agent based behavior simulation - Meng, Xiaoyan; Zhang, Yuting; Meng, Fanxin; Zheng, Xinzhu; Guo, Jianxin (Journal of cleaner production, 2024)
Rapid industrialization and urbanization drive China's massive urban household solid waste (HSW) generation. Classification and resource recycling of HSW is an effective way to address the “garbage-sieged city” dilemma and promote “urban mineral resources” exploitation. Despite efforts since 2000, HSW sorting and recycling remain at 30%. This study develops a multi-agent based behavior simulation model for HSW classification and recycling, incorporating the interactions and decision-making of key agents, including residents, enterprises, and the government. Taking Suzhou, China as a case study, field surveys were conducted, and behavioral decision-making functions were constructed to simulate micro-behavioral responses and macro-system evolution under different policy incentives, and to predict the implementation effect of domestic waste management approaches, provides the basis for decision-making. The results demonstrate that a combination of waste metering charges, recycling subsidies, and enhanced education program can effectively regulate agent behavior and optimize the system. One year after the implementation of the simulation, the number of “unclassification” residents has dropped from 1.85 million to 250,000 decreased by 86%; the number of “classification deposition” residents has declined from 1.28 million to 1.08 million, reduced by 16%; the number of “selling after classification” residents has risen from 1.05 million to 2.81 million, increased by 63%; the daily waste output per capita has decreased from 1.21 kg to 1.04 kg, reduced by 14%; the recovery rate of resources has been raised from 33.4% to 66.5%. The implementation effects of other policy scenarios are ranked as follows: the metering charge > the recycling subsides > the enhanced education program. The findings provide a basis for decision-making in HSW management. Concerning the metering charge and the recycling subsidies, they can benefit positive interactions encouraged by such economic stimulus. At the same time, it is suggested to strengthen classification and recycling infrastructure, and push forward the integration of HSW classification recycling. •A multi-agent based behavior simulation model for household solid waste recycling is developed.•Behavioral decision-making functions were constructed taking Suzhou as a case study.•The implementation effects of four policy scenarios were dynamically evaluated using the model.•Ways and policy suggestions on promoting classification of HSW in China are proposed.